Penyuluhan Kesehatan pada Ibu Hamil Tentang Pemberian ASI Eksklusif - Marlina Marlina; Yusnidaryani Yusnidaryani; Anda Syahputra; Cut Reka Novinda; Eriska Apelino (Syntax Corporation Indonesia, 2023)
The target audience for the Community Partnership Program (PKM) are pregnant women who are in the working area of the Syamtalira Aron Health Center, totaling 30 people. The aim of implementing activities is to improve the quality of human resources through exclusive breastfeeding by increasing knowledge about exclusive breastfeeding, increasing knowledge about breast care during pregnancy and postpartum, increasing skills about breast care during pregnancy and postpartum. The method that will be used to address the problems of the target audience is the Implementation of Community Service which will be carried out by means of health counseling to pregnant women about exclusive breastfeeding and demonstrations of breast care for women during and after childbirth in the working area of the Syamtalira Aron Health Center, North Aceh district. On the first day, before the counseling was carried out, a pre-test was carried out first, and on the second day, a demonstration of breast care was carried out, after which it was continued with a post-test. This activity was carried out from 5 to 6 September 2022, after evaluating an increase in knowledge of 70% and skills of 76.6%, the expected achievement targets were successful. The output that is expected to be achieved from this activity is National publications with ISSN and e-ISSN. Obtain IPR for health education modules and leaflets on exclusive breastfeeding and breast care leaflets during pregnancy and postpartum. Publication has been done through online media. This program is expected to provide benefits to the community, especially the target audience, thereby increasing the quality of human resources.